Предмет: Алгебра,
автор: ангел2445
х^5+3 х^4-8х^3-24 х^2+16х+48=0 решите плиз
Ответы
Автор ответа:
0
х⁵+3х⁴-8х³-24х²+16х+48=x⁴(х+3)-8х²(x+3)+16(х+3)=
=(x+3)(x⁴-8x²+16)=(x+3)(x²-4)²=(x+3)(x-2)²(x+2)²=0.
Ответ: {-3; -2; 2}.
=(x+3)(x⁴-8x²+16)=(x+3)(x²-4)²=(x+3)(x-2)²(x+2)²=0.
Ответ: {-3; -2; 2}.
Похожие вопросы
Предмет: Химия,
автор: jojo8519
Предмет: Математика,
автор: sofiiazasoda
Предмет: Английский язык,
автор: lolipoooppo17
Предмет: Обществознание,
автор: sadaertuil
Предмет: Физика,
автор: sanyok2025